Chemoselective acylation of N-acylglutarimides with N-acylpyrroles and aryl esters under transition-metal-free conditions. Issue 22 (24th September 2021) - Li, Jie; Yao, Jiaqi; Chen, Lingfeng; Zou, Dong; Walsh, Patrick J.; Liang, Guang
Abstract : The imide moiety is a well-known structural motif in bioactive compounds and a useful building block in a variety of processes. Abstract : The imide moiety is a well-known structural motif in bioactive compounds and a useful building block in a variety of processes. Using N -acylglutarimides with MN(SiMe3 )2 and either N -acylpyrroles or aryl esters, an operationally convenient method to produce a wide array of diaryl- and alkyl arylimides is presented. Symmetric imides are also accessible when N -acylglutarimides are employed as acylation reagents under similar reaction conditions. A unique feature of this method stems from the use of two different electrophilic acylating reagents leading to the formation of the unsymmetrical imides with excellent chemoselectivity.